2019
DOI: 10.1080/10538712.2019.1592272
|View full text |Cite
|
Sign up to set email alerts
|

Is Female Psychopathy Linked with Child Abuse? An Empirical Investigation using a Person-Centered Approach

Abstract: Childhood abuse is associated with increased psychopathic features among girls, but most prior research is based on data from correctional samples of female delinquents and less is known about how specific forms of childhood abuse affect specific features of psychopathy. Using a school-based community sample of 696 girls aged 9-17 years from Barbados and Grenada, the current study examined latent profiles of psychopathic personality traits and their associations with physical, emotional, and sexual abuse. Late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…First, there is evidence that traumatic experiences increase psychopathic features among youth, but the effects of specific forms of abuse and neglect are differential and inconsistent (Boduszek et al, 2019; Bonner et al, 2020; Farina et al, 2018; Kerig et al, 2012; Krischer & Sevecke, 2008; Metcalf et al, 2020). For instance, Boduszek et al’s (2019) study of a community sample of girls found that sexual abuse conferred 116% increased likelihood of membership in a high psychopathy latent group and 57% increased odds of psychopathy in a latent group characterized by high interpersonal manipulation and egocentricity. On the other hand, physical and emotional abuse had no associations with psychopathic features.…”
Section: Psychopathy and Trauma Among Youthmentioning
confidence: 99%
“…First, there is evidence that traumatic experiences increase psychopathic features among youth, but the effects of specific forms of abuse and neglect are differential and inconsistent (Boduszek et al, 2019; Bonner et al, 2020; Farina et al, 2018; Kerig et al, 2012; Krischer & Sevecke, 2008; Metcalf et al, 2020). For instance, Boduszek et al’s (2019) study of a community sample of girls found that sexual abuse conferred 116% increased likelihood of membership in a high psychopathy latent group and 57% increased odds of psychopathy in a latent group characterized by high interpersonal manipulation and egocentricity. On the other hand, physical and emotional abuse had no associations with psychopathic features.…”
Section: Psychopathy and Trauma Among Youthmentioning
confidence: 99%
“…There is an ancient Thai proverb, “If you love your cow, tie it up; if you love your child, beat them.” The proverb exemplifies the cultural beliefs and values that encourage physical abuse and preserve its use in Thai culture. Child abuse affects not only the child's psychological, somatic, and social well-being, but also affects the later adult development leading to many negative long-term psychological and emotional consequences for victim, which leads to the increased likelihood of the abused becoming the abusers and finally contributes to negative behaviors and life outcomes [1, 2, 3, 4, 5, 6, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Latent profile analysis (LPA) is an emerging person-oriented method to interpret how some continuous variables combine conjointly within individuals. LPA assumes population heterogeneity and aims to identify latent subgroups within a population by a set of continuous variables (Debowska et al, 2017;Boduszek et al, 2019;Hofmans et al, 2020). Compared with the traditional person-centered method (e.g., cluster analysis), LPA can provide a more accurate and objective classification based on a formal model (Magidson and Vermunt, 2002;Hofmans et al, 2020).…”
Section: The Person-centered Approach In the Calling-related Domainmentioning
confidence: 99%